2016
DOI: 10.1377/hlthaff.2015.1496
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Of Prescription Drug Monitoring Programs Associated With Reductions In Opioid-Related Death Rates

Abstract: Over the past two decades the number of opioid pain relievers sold in the United States rose dramatically. This rise in sales was accompanied by an increase in opioid-related overdose deaths. In response, forty-nine states (all but Missouri) created prescription drug monitoring programs to detect high-risk prescribing and patient behaviors. Our objectives were to determine whether the implementation or particular characteristics of the programs were effective in reducing opioid-related overdose deaths. In adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
250
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(254 citation statements)
references
References 25 publications
2
250
1
1
Order By: Relevance
“…Yet, in spite of these limitations, this study offers important insight into opioid overdoses. Specifically, our findings are consistent with a growing body of research suggesting that while increased regulation of prescription opiates can reduce the likelihood of these substances to be present in overdoses, [29][30][31] it also results in nonmedical prescription opiate users-those using prescription opiates, without a prescription, for the purposes of experiencing or feeling the effects of the drug-turning to illicit opioids. [32][33][34][35] …”
Section: Discussionsupporting
confidence: 88%
“…Yet, in spite of these limitations, this study offers important insight into opioid overdoses. Specifically, our findings are consistent with a growing body of research suggesting that while increased regulation of prescription opiates can reduce the likelihood of these substances to be present in overdoses, [29][30][31] it also results in nonmedical prescription opiate users-those using prescription opiates, without a prescription, for the purposes of experiencing or feeling the effects of the drug-turning to illicit opioids. [32][33][34][35] …”
Section: Discussionsupporting
confidence: 88%
“…No association was found between OA deaths and PDMPs that ranked in the lower half of PDMP strength [2]. Patrick et al [10] found PDMPs to be associated with a reduction of 1.12 OA-related deaths per 100 000 population, or approximately 3000 per year. However, this reduction dropped to 0.18 OA-related deaths per 100 000 and was not statistically significant when West Virginia was excluded from the analysis [10].…”
mentioning
confidence: 98%
“…Patrick et al [10] found PDMPs to be associated with a reduction of 1.12 OA-related deaths per 100 000 population, or approximately 3000 per year. However, this reduction dropped to 0.18 OA-related deaths per 100 000 and was not statistically significant when West Virginia was excluded from the analysis [10]. Both recent analyses were limited to OA-related death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many early states did not require real-time updates or reporting of the system, making the timely dissemination of information or utility for identifying physician and pharmacy shopping limited. 25 Similarly, states tend not to require PDMP participation; as of May 2016, only 29 states require prescribers to register. 26 Moreover, only 34 of the states with PDMPs mandate their use by prescribers or dispensers who are registered in the state.…”
Section: Enhancing Prescription-drug Monitoring Programsmentioning
confidence: 99%